Matahari dalam Perspektif Sains dan Al-Qur'an - Afida, Anisa Nur; yuberti, yuberti; Mustari, Mukarramah (Indonesian Journal of Science and Mathematics Education, 2019)
Abstract: This study aims to determine the function of the sun in the perspective of science and al-Qur'an . The research method used is qualitative research methods with the type of research library (Library Research). This research applies data analysis technique of Milles and Huberman model, with steps: 1) data reduction; 2) data display; 3) verification. The result of this research is, the theories that science explain related to the function of the sun in accordance with what is also described in the Qur'an. Science explains that the sun as the greatest source of light for the earth can produce its own energy. This is explained in the Qur'an that the sun is described as siraj and dhiya' which means sunlight is sourced from itself, as the center of the solar system is not static but also moves this matter in the Qur'an explained in QS Yāsin verse 38, besides science and the Qur'an also equally explain that the sun can be made as a calculation of time.Abstrak: Penelitian ini bertujuan untuk mengetahui fungsi matahari dalam perspektif sains dan al-Qur’an..Metode penelitian yang digunakan yaitu metode penelitian kualitatif dengan jenis penelitian pustaka (Library Research). Penelitian ini menggunakan teknik analisis data model Milles dan Huberman, dengan langkah-langkah: 1) reduksi data; 2) display data; 3) verifikasi. Hasil dari penelitian ini yaitu, teori-teori yang sains jelaskan berkaitan dengan fungsi matahari sesuai dengan apa yang juga di jelaskan dalam al-Qur’an. Sains menjelaskan bahwa matahari sebagai sumber energi cahaya terbesar bagi bumi dapat menghasilkan energinya sendiri hal ini dijelaskan dalam al-Qur’an bahwa matahari dideskripsikan sebagai siraj dan dhiya’yang berarti sinar matahari bersumber dari dirinya sendiri, sebagai pusat tata surya matahari tidaklah statis melainkan juga bergerak hal ini dalam al-Qur’an di jelaskan dalam QS Yāsin ayat 38, selain itu sains dan al-Qur’an juga sama-sama menjelaskan bahwa matahari  dapat di jadikan sebagai perhitungan waktu serta petunjuk dari bayang-bayang.